Decision making reflecting the fractalization of the society - Kalina, Jan (Serbian Journal of Management, 2022)
Although the mainstream economic doctrine relies on the concept of equilibrium, the current society has been recently facing serious challenges. While we can experience a gradually rise of the ideals of the knowledge society, we hold the opinion that the society (and the economies worldwide as well) will have a fractal structure following models investigated by the chaos theory. This paper is focused on decision making especially in economic or managerial tasks and its transforms due to the paradigm shift towards a fractal society in disequilibrium economic conditions. Statistical and information-theoretical aspects of decision support are discussed and a decision making example from the field of credit risk management is analyzed and presented.
Keywords: decision support; economic equilibrium; management; credit risk; information theory; chaos theory